Community-Based Rehabilitation (CBR) in primary care centers in Chile - Álvaro Besoain-Saldaña; Jame Rebolledo Sanhueza; Mónica Manríquez Hizaut; Valentina Cortínez Rojas; Gabriela Huepe Ortega; Verónica Aliaga-Castillo (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To describe the implementation status of the Community-Based Rehabilitation in Chile. METHODS Quantitative, transversal and descriptive study. The scope was constituted by the 66 community-based rehabilitation centers in the Chilean Metropolitan Region that implemented Community-Based Rehabilitation until December 2016. The sampling was based on a census method, so all the community centers were contacted. A self-administered questionnaire designed based on the Community-Based Rehabilitation matrix defined by the World Health Organization was applied. The questionnaire was answered on-line by the coordinators of the strategy in their respective centers. The data analysis was performed using descriptive statistics. RESULTS A heterogeneous level of implementation of Community-Based Rehabilitation was identified, specifically in terms of the components of the matrix described by the World Health Organization. The most implemented component was Health; the Social, Livelihood and Empowerment components were moderately implemented; and the Education component was the least implemented. CONCLUSION The implementation of Community-Based Rehabilitation is mainly based on the Health component. The level implementation of the other components of the matrix needs to be increased, as well as interdisciplinary and intersectoral strategies to achieve greater social inclusion of people with disabilities.